2019
DOI: 10.3899/jrheum.190407
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Takayasu Arteritis Patients with Severe Ischemic Events

Abstract: Objective Takayasu arteritis (TA) is a rare large-vessel vasculitis that puts patients at high risk of developing severe ischemic events (SIE). Outcomes for TA patients with SIE are poorly understood. We aim to describe the characteristics of TA patients experiencing SIE. Methods All TA patients with at least 1 followup visit seen between 1988 and 2015 were included from 3 academic centers in Ontario, Canada. Diagnosis was based on American College of Rheumatology criteria, physician opinion, and vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Interestingly, our results revealed no significant difference in the mean ESR level between TA patients with and without MACCEs during the follow-up period, nor was there any significant association between corticosteroid dose (high-dose vs. low-dose) and the occurrence of MACCEs. A recent study conducted by Yu et al [36] on 52 TA patients, reported that 15 (29%) of these patients experienced a severe ischemic event (ISE) within the 6-year follow-up period, of which 5 experienced CVA, 5 encountered acute coronary syndrome (ACS), 1 exhibited ischemic cardiomyopathy, and 5 experienced limb ischemia. They further investigated the potential predictors of ISE in TA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results revealed no significant difference in the mean ESR level between TA patients with and without MACCEs during the follow-up period, nor was there any significant association between corticosteroid dose (high-dose vs. low-dose) and the occurrence of MACCEs. A recent study conducted by Yu et al [36] on 52 TA patients, reported that 15 (29%) of these patients experienced a severe ischemic event (ISE) within the 6-year follow-up period, of which 5 experienced CVA, 5 encountered acute coronary syndrome (ACS), 1 exhibited ischemic cardiomyopathy, and 5 experienced limb ischemia. They further investigated the potential predictors of ISE in TA patients.…”
Section: Discussionmentioning
confidence: 99%